PROCESSO JUDICIAL: A ANÁLISE DE DISPOSITIVOS DE MODALIZAÇÃO NAS INTERAÇÕES INTERPESSOAIS NOS JUIZADOS ESPECIAIS CRIMINAIS - Silva, Ana Rafaela Rodigues da; Colares, Virgínia (Intercâmbio, 2010)
This research has the aim of studying the legal speech based on the analysis of authentic verbal data. The proposal justifies itself through the moving of the ideal and aprioristic hypothetical construction of the legal tradition to an empiric-scientific analysis, through the critical analysis of the speech methodology.